System to propose the final grade of the students through Neural Networks - Baldarrago Salas, Kleber Ernesto (2021)
Due to the recurring problem presented in the students regarding their academic performance, an application of neural networks was developed with the aim of helping the teacher, since it is capable of giving results of the final grades of the students and will help the teacher to understand the reason for the results, since this neural network takes into account different factors that lead the student to have a passing or failing grade. To obtain the results, we worked on the training of the neural network through the classification model which shows in the result the number of approved or disapproved students and the other regression model which predicts a student's grade given the characteristics of their initial survey, both models were of great help in predicting the behavior of the data.